PRESENTATION - Editors, The (Revista Eletrônica: Tempo - Técnica - Território / Eletronic Magazine: Time - Technique - Territory, 2017)
To plan and to implement academic projects remain a systematic challenge for the team and the collaborators of the Electronic Journal. Each study published is an opportunity to strengthen the proposed goals and to add more value to the community involved and interested.